Carbon Mineralization and Inorganic Nitrogen Pools under Terminalia chebula Retz.-Based Agroforestry System in Himalayan Foothills, India. Issue 5 (20th June 2020) - Kumar, Amit; Dwivedi, Gopal Krishna; Tewari, Salil; Paul, Jai; Anand, Rahul; Kumar, Narendra; Kumar, Parmanand; Singh, Hukum; Kaushal, Rajesh
Abstract: Soil organic matter is major terrestrial pool for soil organic carbon (C) and nitrogen (N), and their decomposition is sensitive to vegetation and climate change. Integrated nutrient management (INM) deals with the combined application of chemical fertilizers and organic manures for nutritional requirement of crops and avoid the adverse effect of long-term application of chemical fertilizer on crop production and their sustainability. The present study was carried out to investigate the influence of different nutrient sources on soil C mineralization and inorganic N pools in a Terminalia chebula Retz, based on a agroforestry system. The results showed that the highest CO2 evolution was recorded in 100 percent INM and minimum in farmyard manure treatment after 120 days of incubation. Inorganic N was higher under the agroforestry system than under the open system. Among the different nutrient sources, the highest inorganic N was recorded in a 100 percent INM nutrient source and minimal in wheat straw treatment. The yield of turmeric was higher under the T. chebula -based agroforestry system (20.87 t ha –1 ) than under the open system (19.27 t ha –1 ). Results suggest that agroforestry systems using the INM approach can enhance C mineralization and inorganic N concentration with improved crop productivity in the Himalayan foothills. Study Implications: Fertilizer has been used since ancient times, and if well managed it can be an asset, promoting sustainable agriculture and increasing crop production, particularly for smallholder farmers in the Himalayan region of India. We compared fertilizer application practices under an agroforestry system in a representative Himalayan region of India. The majority of farmers in the region of the Himalayan foothills having marginal land and they are not able to produce optimum food grains for their requirement. However, their demands are increasing day by day, so to fulfill their demand, they have to adopt agroforestry. Agroforestry may be fulfilling their demand in terms of food, fuel, fodder, and other intangible benefits. Moreover, to increase the production under agroforestry, we have to apply organic and inorganic fertilizer in the soil either as the sole application or as a combination of these fertilizers. The application of these fertilizers will improve the productivity and fertility of land, especially carbon mineralization and inorganic nitrogen. These two soil properties are important to study because these are limiting to land productivity. In addition, efforts to improve integrated nutrient management in the Himalayan region of India would strengthen farmers' incomes by strengthening land fertility and productivity. The rapid increase in human population over the last century is putting a massive pressure on existing resources, namely soil and water, resulting in environmental degradation in some regions around the world. As productive land becomes scarce, marginalized farmers are pushed into fragile croplands and forest lands unsuitable for modern agriculture which, in turn, is vulnerable, to degradation. If the present trend in population growth persists, pasture and forest lands will be further reduced (Satterthwaite et al. 2010 ). At this stage, the value of growing trees becomes more significant, and participation in tree planting schemes should be encouraged. However, this option is most feasible when combined with agriculture. As a result, agroforestry is an important management strategy that not only helps to meet the world food requirements but also helps to protect soil from degradation (Ram et al. 2017 ) and can enhance soil organic matter levels by adding the quantity of above- and below-ground organic matter inputs to soils (Nair et al. 2009, Marone et al. 2017 ).